The Complexity of Fulfilling the Constitutional Rights of Street Vendors by Local Governments in Indonesia - Wardhana, Allan Fatchan Gani; Retno Widiastuti; Yuniar Riza Hakiki (Universitas Islam Negeri Raden Intan Lampung, 2025)
Regulation of street vendors (PKL) remains limited. On the other hand, street vendors are closely related to micro, small, and medium enterprises, traffic, and spatial planning, thereby requiring local governments in manage the complexity of street vendors' affairs in line with the fulfillment of their constitutional rights. This research aims to identify the complexity of street vendor arrangement and empowerment policies that are in line with the active role of local governments in providing fulfillment of rights for street vendors, and to formulate a reformulation of street vendor arrangement and empowerment in a more appropriate local government frame. This research employs a juridical-normative approach, combining a statutory and a conceptual approach to address the complexity of fulfilling constitutional rights for street vendors in the regions. The fulfillment of constitutional rights through the arrangement and empowerment of street vendors in the areas is very complex. Regional policies are also very complex because they involve various sectors. The business characteristics of street vendors, which were originally informal, have evolved into formal trade. Both in terms of legal status, business legality, business arrangements and locations, and governance complexity. The arrangement and empowerment of street vendors need to be reformed and incorporated in the Law on Regional Government by categorizing them as a sub-concurrent government affair in the field of trade.